Serum lactate as predictor and diagnostic biomarker of plasma leakage in adult dengue patients - Bur, Rika; Suwarto, Suhendro; Santoso, Widayat Djoko; Harimurti, Kuntjoro (Universa Medicina, 2016)
Background Dengue fever (DF) and dengue hemorrhagic fever (DHF) are differentiated by the occurrence in DHF of plasma leakage into the interstitial space as shown by pleural and peritoneal effusion, hemoconcentration, and intravascular hypovolemia. Perfusion dysfunction causes anaerobic metabolism, which leads to increased serum lactate. This study was to determine serum lactate as prognostic predictor and diagnostic biomarker of plasma leakage in adult dengue patients.Methods A cross-sectional retrospective cohort study was conducted on 57 adult dengue patients hospitalized in the internal medicine ward of Cipto Mangunkusumo Hospital and Persahabatan Hospital in Jakarta. Serum lactate was examined to determine its mean difference between DF and DHF. The data was analyzed by independent t-test and the cut-off points were identified for presence as well as absence of plasma leakage, then the receiver operating characteristics (ROC) curve was used to determine sensitivity and specificity.Results Mean serum lactate was significantly higher in DHF than in DF. From the ROC curve, the cut-off point for serum lactate as prognostic predictor on day 3 of fever was Â³2.65 mmol/L with AUC of 0.626 (95% CI 0.480-0.772; p=0.108). The cut-off point for diagnostic biomarker of plasma leakage on day 5 of fever was 2.55 mmol/L with sensitivity 66.6%, specificity 54.2%, and AUC 0.668 (95% CI 0.550-0.826; p=0.016).Conclusion There was a significant difference in serum lactate between DF and DHF. In the critical phase, serum lactate of 2.55 mmol/L could be used as plasma leakage diagnostic marker of low accuracy.